Relationship between levels of maternal serum un-conjugated estriol and gestational diabetes mellitus - Azam Amirian; Nourossadat Kariman; Mehdi Hedayati; Nasrin Borumandnia; Zahra Naeje (Mashhad University of Medical Sciences, 2019)
Introduction: Gestational diabetes is the most common medical condition during pregnancy. Early diagnosis and preventive and therapeutic measures reduce the short-term and long-term complications of mother, fetus and infant. This study was performed with aim to determine the relationship between un-conjugated estriol and gestational diabetes. Methods: This case-control study was conducted on 60 pregnant women with gestational diabetes mellitus (case group) and 120 healthy pregnant women (control group) referred to Mahdieh and Taleghani hospitals of Tehran in 2017-2018. Triple test was performed for the samples in 14-17 weeks of gestation and oral glucose tolerance test with 75 g glucose was performed in 24-28 weeks of gestation. Data were collected by interview. Data were analyzed using SPSS software (version 17) and independent t-test, Chi-square, Mann-Whitney, and logistic regression. P < 0.05 was considered significant. Results: Mean and standard deviation of un-conjugated estriol in case group was 1.17 ± 0.61 and in control group was 1.02 ± 0.47 MOM. The level of un-conjugated estriol was significantly higher in the case group than the control group (p = 0.011). Conclusion: Increased level of un-conjugated estriol in early pregnancy can be suggested and evaluated as a new diagnostic test for gestational diabetes. Therefore, performing the necessary measures can reduce its complications by early identification of at-risk women.